Auto-detection of sporadic E and spread F events from the digital ionograms. Issue 4 (15th August 2022) - Venkateswara Rao, T.; Sridhar, M.; Venkata Ratnam, D.
Abstract: To evaluate huge ionogram datasets and detect ionosphere variabilities, automatic identification of Sporadic E (Es) and Spread F (SF) events in digital ionograms is required. This work presents an auto-detection technique to identify the ionograms' Es and SF signatures. Es and SF events are detected automatically by de-noising the ionogram, segmentation, and quantifying the frequency and height points in each layer segmented part. The technique's performance is assessed using ionograms acquired by the Canadian Advanced Digital Ionosonde (CADI) at a low latitude station in Hyderabad, India, in 2015. With a detection efficiency of 96.71%, 89.71%, and 93.39%, the suggested technique successfully detected the Es, Range Spread F (RSF), and Strong Spread F (SSF) events from ionograms. To demonstrate the correlation between SSF and S4, the occurrence rate of SSF is compared to the amplitude scintillation (S4) rate of the Global Positioning System (GPS). The recommended technique is useful for launching ionospheric alert systems for high-frequency communications and GPS users.